Integration of corporate social responsibility and digital marketing in the floriculture sector - Frías Pérez, Edisson Andrés (2025)
Corporate Social Responsibility (CSR) has evolved to become a fundamental pillar of modern corporate strategies. At the same time, digital marketing has established itself as an essential tool in the digital age, allowing companies to establish more direct and personalized connections with their consumers. The objective of the study was to determine the relationship between the Integration of Corporate Social Responsibility and Digital Marketing in the Floriculture Sector of Ecuador. Its approach is quantitative, descriptive, correlational design. The population was 308 people. A survey with closed questions was applied. The results reveal that the integration of CSR and digital marketing presents challenges, such as the need for authenticity and consistency in messages. The conclusions demonstrate that, when carried out in an authentic, continuous and strategic manner, the integration of CSR with digital marketing can offer significant benefits for both companies and society in general